2013
DOI: 10.3748/wjg.v19.i11.1827
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter case-control study of the risk factors for ulcerative colitis in China

Abstract: Our study showed tap water consumption was a protective factor for UC, while spicy food, heavy sugar consumption and often feeling stress were risk factors for UC in this Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
2
46
1
2
Order By: Relevance
“…The present study identified a significant probability of low fruit and high refined sugar intake to be associated with UC similar to other (including Asian) studies [9][10][11][12][13] . The possible mechanism of protection is by antioxidant vitamins and fibres contained in these foods.…”
Section: Discussionsupporting
confidence: 75%
“…The present study identified a significant probability of low fruit and high refined sugar intake to be associated with UC similar to other (including Asian) studies [9][10][11][12][13] . The possible mechanism of protection is by antioxidant vitamins and fibres contained in these foods.…”
Section: Discussionsupporting
confidence: 75%
“…Comparison I was conducted among 11 studies (5)(6)(7)19,25,27,28,(30)(31)(32)34) with 10,889 subjects (UC patients: 4,673; healthy control: 6,216). …”
Section: The Results Of Comparison I: Appendectomy Was a Protective Fmentioning
confidence: 99%
“…Then, 321 completely unrelated studies and 140 reviews, letters or abstracts were excluded, and 45 articles remained. By screening of the full text, 19 studies were finally included in the present meta-analysis (5)(6)(7)(15)(16)(17)19,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The basic information of the selected studies is listed in tables I-III.…”
Section: Study Selectionmentioning
confidence: 99%
“…The characteristics of the final nine studies selected for analysis are shown in Table 1 (15)(16)(17)(18)(19)(20)(21)(22)(23). Two cohort and seven case-control studies were included.…”
Section: Literature Review and Study Characteristicsmentioning
confidence: 99%
“…The nine studies reported a total of 2,019 cases of UC, 683 of CD, and 160 of IBD. Data was obtained from Asian (n=4) (15)(16)(17)21) and European (n=5) populations (18-20, 22, 23). Of the nine studies, five examined total meat consumption (15-17,19,21,23), three only examined red meat consumption (18,20,22), two examined processed meat consumption (22,23), and two only examined white meat consumption (18,20).…”
Section: Literature Review and Study Characteristicsmentioning
confidence: 99%